Electrical study on Carboxymethyl Cellulose-Polyvinyl alcohol based bio-polymer blend electrolytes - M. A., Saadiah; Ahmad Salihin, Samsudin (IOP Publishing Ltd, 2018)
The present work deals with the formulation of bio-materials namely carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) for bio-polymer blend electrolytes (BBEs) system which was successfully carried out with different ratio of polymer blend. The biopolymer blend was prepared via economical & classical technique that is solution casting technique and was characterized by using impedance spectroscopy (EIS). The ionic conductivity was achieved to optimum value 9.12 x 10-6 S/cm at room temperature for sample containing ratio 80:20 of CMC:PVA. The highest conducting sample was found to obey the Arrhenius behaviour with a function of temperature. The electrical properties were analyzed using complex permittivity ε* and complex electrical modulus M* for BBEs system and it shows the non-Debye characteristics where no single relaxation time has observed.